Is Sexual Conflict a Driver of Speciation? A Case Study With a Tribe of Brush-footed Butterflies. (3rd September 2020) - Carvalho, Ana Paula S; St Laurent, Ryan A; Toussaint, Emmanuel F A; Storer, Caroline; Dexter, Kelly M; Aduse-Poku, Kwaku; Kawahara, Akito Y
Abstract: Understanding the evolutionary mechanisms governing the uneven distribution of species richness across the tree of life is a great challenge in biology. Scientists have long argued that sexual conflict is a key driver of speciation. This hypothesis, however, has been highly debated in light of empirical evidence. Recent advances in the study of macroevolution make it possible to test this hypothesis with more data and increased accuracy. In the present study, we use phylogenomics combined with four different diversification rate analytical approaches to test whether sexual conflict is a driver of speciation in brush-footed butterflies of the tribe Acraeini. The presence of a sphragis, an external mating plug found in most species among Acraeini, was used as a proxy for sexual conflict. Diversification analyses statistically rejected the hypothesis that sexual conflict is associated with shifts in diversification rates in Acraeini. This result contrasts with earlier studies and suggests that the underlying mechanisms driving diversification are more complex than previously considered. In the case of butterflies, natural history traits acting in concert with abiotic factors possibly play a stronger role in triggering speciation than does sexual conflict. [Acraeini butterflies; arms race; exon capture phylogenomics; Lepidoptera macroevolution; sexual selection; sphragis.]